THE EFFECT OF PROFESSIONALISM, OBJECTIVITY, ACCOUNTABILITY, KNOWLEDGE OF THE ACCURACY OF GIVING AUDIT OPINION AND AUDITOR EXPERIENCE AS MODERATING VARIABLES - Hari Stiawan; Aris Sanulika (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2019)
The auditor as a party trusted by the public, the auditor will examine the financial statements and then issue a statement. This study aims to determine the effect of professionalism, objectivity, accountability, knowledge on the accuracy of the provision of audit opinions and auditor experience as a moderating variable on the influence of audit expertise on the accuracy of giving opinions by the auditor. The type of data used in this study is quantitative data. Sources of data in this study are primary data. The population in this study were auditors who worked at KAP located in South Tangerang. With the number of respondents in this study as many as 58 people. The results of this study indicate that professionalism, objectivity, accountability, knowledge do not influence the accuracy of giving audit opinions either partially or partially. The auditor's experience can moderate the variables of professionalism, objectivity, accountability, knowledge of the accuracy of the giving of